Psychologically informed oral health interventions in pregnancy and type 2 diabetes: A scoping review - Kristensen, Camilla Böhme; Ide, Mark; Forbes, Angus; Asimakopoulou, Koula (Frontiers in Oral Health, 2022)
Introduction: Oral health is a critical aspect of gestational diabetes management. Gestational diabetes is high blood glucose levels during pregnancy and is managed like type 2 diabetes with diet and physical activity interventions. This scoping review sets out to discuss why oral health support should also become part of gestational diabetes management. Objectives: The primary objective was to synthesise the existing psychologically informed oral health interventions for pregnant women and individuals with type 2 diabetes, and the extent to which these interventions map on to the COM-B Model. No literature exists on oral health interventions in gestational diabetes, why studies with type 2 diabetes populations were selected instead. The secondary objective was to identify the precise outcomes targeted in the interventions. Methodology: The Joanna Briggs Institute’s Methodology for Scoping Reviews was used to conduct this review. The populations of interest were pregnant women and individuals with type 2 diabetes, and eligible concepts were psychologically informed oral health interventions. Quasi-experimental and experimental designs were considered. The Ovid Interface including Embase, Medline, Global Health, APA PsychInfo, Health Management Information, Maternity, Infant Care Database, the Cochrane Library, and CINAHL was used as information sources. The study selection followed the PRISMA guidelines. The first search was conducted on the week commencing the 25th of July 2022, with a follow-up search conducted on the 10th of October 2022. Results: 28 records were included for synthesis. The most frequently assessed psychological outcome was oral health knowledge and the most frequently assessed oral clinical outcome was Plaque Index. All studies used an educational intervention approach, while psychological capability in the COM-B Model was targeted in all interventions by increasing oral health knowledge among the participants. The Health Belief Model was the most frequently used theory in the interventions. Conclusion: The results demonstrate that oral health is a recognised aspect of pregnancy and type 2 diabetes. The findings from this review and a qualitative interview study which is under development will inform the first oral health intervention for women with gestational diabetes in the United Kingdom.